The Surgical Management of Large Bladder Calculi and Irreducible Uterine Prolapse: A Case Report and Review of Literature - Komon W. (2023)
Bladder calculi are rare in women. We report a case of bladder calculi complicating irreducible uterovaginal prolapse. It provides diagnostic and operative challenges to the management team. A 77-year-old woman presented with irreducible complete uterovaginal prolapse. Bladder stones were appreciated on examination and confirmed with imaging. The patient was managed surgically with transabdominal hysterectomy with bilateral uterosacral colpopexy followed by cystolithotomy. The patient's postoperative course was uncomplicated, and she had an uneventful recovery at her 3-month postoperative visit without a recurrence of prolapse and gained good continence. The presence of bladder calculi should be considered in the setting of irreducible pelvic organ prolapse. The abdominal approach of cystolithotomy with a concomitant hysterectomy and vaginal apical suspension is safe and effective.